1943
DOI: 10.1128/jb.45.4.309-320.1943
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Anaerobes and Oxidation-Reduction Potentials

Abstract: In the cultivation of anaerobes in fluid media exposed to air it has been customary for some time to poise the medium at a favourable oxidation-reduction potential level by the addition of reducing agents or to retard diffusion of oxygen by the addition of agar to the medium. Allwin and Baldwin (1930) reviewed the use of reducing agents some ten years ago. Since that time, other agents have been introduced, particularly ascorbic acid (Klinger and Guggenheim, 1935) sodium thioglycollate and sodium formaldehyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1953
1953
1986
1986

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…It may supply a surface where nutrients can accumulate in optimal concentrations. Reed and Orr (1943) observed that twice the concentration of cells of various species of Clostridium was needed to initiate growth in a medium with only thioglycolate added instead of both thioglycolate and agar. The beneficial effects of soluble starch and bovine serum albumin may result from a * Cells harvested from passage medium by centrifugation, washed twice with 0.85 per cent saline and diluted in saline.…”
Section: Resultsmentioning
confidence: 99%
“…It may supply a surface where nutrients can accumulate in optimal concentrations. Reed and Orr (1943) observed that twice the concentration of cells of various species of Clostridium was needed to initiate growth in a medium with only thioglycolate added instead of both thioglycolate and agar. The beneficial effects of soluble starch and bovine serum albumin may result from a * Cells harvested from passage medium by centrifugation, washed twice with 0.85 per cent saline and diluted in saline.…”
Section: Resultsmentioning
confidence: 99%
“…It seems reasonable to explain this on the supposition that it takes time for an isolated cell to reduce the redox potential in its immediate vicinity to a point where development can begin, while, once this is under way, the cells can maintain strongly reducing conditions in the vital region regardless, within limits, of the potential in the medium as a whole. Reed & Orr (1943) demonstrated this with C1. welchii by heavily inoculating a poorly poised peptone-phgsphate medium (E, +225 mV, pH 7.6) and then centrifuging a t high speed for 30 min so that the organisms were packed around platinum electrodes inserted through the base of the tubes, when the redox potential fell to E, -200 mV in the sediment.…”
Section: Discussionmentioning
confidence: 74%
“…welchii and a t pH 6.0-6.2 the highest potential a t which growth was recorded was about + 130 mV in a glucose, peptone, meat extract medium. Reed & Orr (1943) were able to obtain growth with Cl. welchii a t +ZOO to 4-250 mV (pH 7.6) when a very heary inoculuni was used, but were unable to get growth from small inocula a t high E, levels.…”
Section: Discussionmentioning
confidence: 99%
“…The models presented in this paper do not include the physical fermentation variables, pH and the redox potential (Eh). These two parameters have been shown to be among the most important factors in the control of the culture performance and solvent biosynthesis Andresch et al, 1982;Reed and Orr, 1943). In a batch culture the change in the fermentation from the acidogenic phase to the solventogenic phase does not occur unless pH is in a range of 4.3-5.2.…”
Section: Discussionmentioning
confidence: 99%